IL-2Rα KO mice exhibit maternal microchimerism and reveal nuclear localization of IL-2Rα in lymphoid and non-lymphoid cells - Wong, Victoria A.; Dinh, Kristie N.; Chen, Guangchun; Wrenshall, Lucile E. (Frontiers in Immunology, 2024)
IL-2Ra KO mice have been instrumental to discovering the immunoregulatory properties of IL-2Ra. While initially thought of only as a stimulatory cytokine, IL-2 and IL-2Ra knock out (KO) mice revealed that this cytokine-receptor system controls immune responses through restimulationinduced cell death and by promoting the survival of T regulatory cells. Although described mostly in the context of lymphocytes, recent studies by our laboratory showed that IL-2R is expressed in smooth muscle cells. Given this finding, we sought to use IL-2Ra knock mice to determine the function of this receptor in vascular smooth muscle cells. Surprisingly, we found that IL-2Ra knock out vascular smooth muscle cells had detectable IL-2Ra. Further studies suggested that the source of IL-2Ra protein was likely maternal heterozygous cells present in KO offspring due to maternal microchimerism. Because the KO was generated by using a neomycin resistance gene insert, we treated cells with G418 and were able to eliminate the majority of IL-2Ra expressing cells. This elimination revealed that IL-2Ra KO vascular smooth muscle cells exhibited increased proliferation, decreased size, and hypodiploid DNA content when compared to wildtype cells. Our findings suggest that the phenotype of complete IL-2Ra loss is more severe than demonstrated by IL-2Ra KO mice, and that IL-2Ra plays a here-to-fore unrecognized role in regulating cell proliferation in non-lymphoid cells.